2018
DOI: 10.1016/j.erss.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Prosumer Pathway? Exploring household solar energy development in Germany, Norway, and the United Kingdom

Abstract: Peer-review status of attached le: eerEreviewed Citation for published item: snderergD or r¦ kon tkson nd ewsD uerstin nd urnerD fritt @PHIVA 9ss there rosumer thwyc exploring household solr energy development in qermnyD xorwyD nd the nited uingdomF9D inergy reserh nd soil sieneFD RP F ppF PSVEPTWF Further information on publisher's website: httpsXGGdoiForgGIHFIHITGjFerssFPHIVFHRFHHT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 43 publications
1
35
0
4
Order By: Relevance
“…High costs, lack of regulation, and administrative requirements, were identified as common barriers. Similarly, Inderberg et al [64] investigated prosumer numbers and their correlation with economic incentives, regulatory requirements, and information practices alongside an installer market. This case study approach identified similar trends in stages of prosumer development across three European countries.…”
Section: Theorymentioning
confidence: 99%
“…High costs, lack of regulation, and administrative requirements, were identified as common barriers. Similarly, Inderberg et al [64] investigated prosumer numbers and their correlation with economic incentives, regulatory requirements, and information practices alongside an installer market. This case study approach identified similar trends in stages of prosumer development across three European countries.…”
Section: Theorymentioning
confidence: 99%
“…The Labour government introduced the FiT for small-scale renewables into the 2008 Energy Bill, with effect from 2010. While small-scale generation such as photovoltaics had not previously been accompanied by remuneration, there were several versions of relatively ineffective installation support schemes that targeted household suppliers and small and medium-sized enterprises (Inderberg et al, 2018). The FiT requires electricity suppliers to pay fixed tariffs to small renewable generators for electricity exported to the National Grid.…”
Section: Two Outputs Of the Policy-making Processmentioning
confidence: 99%
“…The debate is heated, particularly in relation to the introduction of the long-term auction-based CfDs, which tend to favour bigger companies. However, the FiT, which was introduced in 2008, has supported small electricity generators and resulted in a high deployment of small-scale production, often by private households (Inderberg et al, 2018). Given these differences, it is interesting to study the renewable energy sector in the UK to understand how access to the political system influences output.…”
Section: Introductionmentioning
confidence: 99%
“…Though the growth of PV and prosumers in Norway has lagged behind other Scandinavia countries, recent research offers insights on the potential for further development. One such study provides an excellent review by examining the historical development of prosumers in Germany, UK and Norway [17]. The study identifies the major determinants of prosumer activity by considering three types of factors: economic incentives (e.g., support schemes, tax benefits, etc.…”
Section: Literature Reviewmentioning
confidence: 99%